Bimbingan Konseling terhadap Anak yang Broken Home: Memetakan Peran dan Fungsi Strategis Pendidikan Kristiani (Sekolah Tinggi Teologi Kerusso Indonesia, 2023)
This research aims to explain the role of Christian Religious Education teachers in implementing counseling guidance. A Christian religious education teacher has particular duties and responsibilities for student education, which is predominantly Christian. Christian Religious Education Teachers not only provide education but also build the character and spirituality of students. In the world of education, many students have different family backgrounds. Some children are born into harmonious families, and others into families that do not support a child's education. Among them is a broken home child who does not have a harmonious family, such as parents who often fight, domestic violence, and parents who choose to divorce; so many problems occur that hinder the child's education, character, and spirituality. Using descriptive qualitative methods, it can be concluded that for this reason, Christian religious education teachers can take part in counseling guidance to help broken-home students so that the student's character and spirituality can grow through individuals who rely on God. AbstrakPenelitian ini bertujuan untuk menjelaskan peran guru Pendidikan Agama Kristen dalam menerapkan bimbingan konseling. Seorang guru pendidikan agama Kristen memiliki tugas dan tanggung jawab khusus bagi pendidikan peserta didik terutama pendidikan Kristen. Guru Pendidikan Agama Kristen bukan hanya memberikan pendidikan tetapi juga membangun karakter dan spiritualitas peserta didik. Dalam dunia pendidikan banyak diantara peserta didik yang memiliki latar belakang keluarga yang berbeda. Sebagian anak terlahir dalam keadaan keluarga harmonis dan yang lain dalam keluarga yang tidak mendukung pendidikan seorang anak. Di antaranya seorang anak broken home yang tidak memiliki keluarga yang harmonis , seperti: orang tua yang sering bertengkar, kekerasan dalam rumah tangga, orang tua yang memilih untuk bercerai, sehingga banyak masalah-masalah yang terjadi yang berhambat pendidikan, karakter dan spiritual anak. Menggunkan metode kualitatif deskritif maka dapat disimpulkan bahwa untuk itu Guru pendidikan agama Kristen dapat mengambil bagian dalam bimbingan konseling untuk menolong peserta didik broken home sehingga karakter dan spiritualitas peserta didik dapat bertumbuh melalui pribadi yang mengandalkan Tuhan.